REASONABLE MANAGEMENT INDEX IN FILL LOADING WITH VACUUM CONSOLIDATION METHOD BASED ON FEM ANALYSES - M. Shahiduzzaman; Y. Tanabashi; H. Kawabata; Y. Jiang; S. Sugimoto (Lowland Technology International, 2010)
Vacuum consolidation method (VCM) is one of the recent methods being utilized for the improvement of soft ground. This method can forcibly drain pore water, and increase ground strength by loading with vacuum pressure. A fill loading with vacuum consolidation method (FLVCM) is reported to be able to control lateral displacement and upheaval of the surrounding area during rapid fill loading. However, the behavior of this combination of benefits on ground deformation is not fully clarified within FLVCM. Fill design and site management depends on experience with the technique. In this study, numerical simulation has been carried out by finite element method (FEM) for the quantitative evaluation of the deformation suppression effect of FLVCM on the soft grounds of Ariake clay in Japan. The utility of FLVCM was confirmed by comparison of observed and analytical ground deformation. In addition, numerical simulations have been carried out under various conditions of vacuum pre- and post-loading pressures and fill speeds. It looks as though a reasonable management index can be easily obtained by site measurement of deformation.